A conceptual model of foreign investment : a forestry internationalization case between New Zealand and Korea : a thesis presented in partial fulfillment of the requirements for the degree of Master of Agricultural Economics at Massey University - Shin, Young-Woo (Massey University, 1994)
The purpose of this thesis is to explore comprehensive, strategic investment structure by examining the factor interactions revolving around the current issues which confront New Zealand forestry internationalisation in the global economic perspectives. This thesis presents the prototype of a conceptual model of international forestry as a modified joint venture\ trust system by examining the existing institutional and legal structure. Considering the global, conceptual nature of this thesis, macro-theoretical and institutional approach were adopted instead of statistical, micro analysis. In order to derive a micro, realistic solution from the macro, global issues, the flow of basic logic and scope of this research has been advanced progressively such as Worldwide (global) --- Asia Pacific Rim (multilateral) Bilateral (eg., New Zealand versus Korea) --- Bilateral arrangement (eg., modified joint venture \ Trust system). Also, basic components and scenarios which are useful to seek out alternatives were proposed to solve the current problems which face New Zealand forestry. The conceptual model which is proposed in this thesis could be tested and applied not only in bilateral but also in multilateral trade and investment relationships by modifying it to adjust to specific circumstances. In this way, the credibility gap between the conceptual model and real world is greatly diminished. Ultimately, the conceptual model could contribute as a useful mechanism to analyse international factor mobility between resource-demanding and supplying countries.
Keywords: New Zealand; Forest products -- Commerce; Korea (South); Forest products industry -- Capital investments; Foreign investments